Consequences of the Chicago consensus on disorders of sex development (DSD): current practices in Europe. Issue 8 (22nd September 2009) - Pasterski, V; Prentice, P; Hughes, I A
Abstract : Objective: To assess clinical management of disorders of sex development (DSD) subsequent to recommendations issued in the 2006 Consensus Statement. Design: Online questionnaire and audit of DSD literature. Setting: Invitation to complete a 28-item online questionnaire and a 12-item follow-up questionnaire, both assessing current clinic statistics and clinical management of DSD. Participants: Paediatric endocrinologists from 60 medical centres representing 23 European countries. Main outcome measures: Clinic activity, multidisciplinary team composition, provision of psychological support services, incidence of feminising clitoroplasty and use of diagnostic algorithms and newly proposed nomenclature. Analyses: Data are reported in terms of percentages with respect to implementation of recommendations outlined in the Consensus Statement. χ 2 was used to analyse changes in nomenclature reported in the literature. Results: 60 centres reported on management of an average of 97.3 (range 8–374) patients per year, totalling approximately 6000. The mean number of new referrals in the previous year was 23.27 (range 8–100). 57% of centres regularly included the services of recommended paediatric subspecialists: paediatric endocrinologist, paediatric surgeon/urologist, plastic surgeon, paediatric psychiatrist/psychologist, gynaecologist, clinical geneticist, histopathologist and neonatologist; 35% reported providing these and additional services of endocrine and surgical nurses, a social worker and a medical ethicist. Additionally, 95% of centres reported offering primary psychological support services (either child psychiatrist or psychologist). 65% of centres reported using a diagnostic algorithm, and 83.3% supported the development of a standardised algorithm. 52% and 44.8% of centres reported having performed fewer or similar numbers, respectively, of clitoroplasties than in previous years and only 3.4% reported an increase. Finally, 100% of respondents reported using the newly proposed terminology. Likewise, an audit of the literature reflected a recent reduction in usage of the non-preferred historical terminology. Conclusions: There is evidence that the majority of European DSD centres have implemented policies and procedures in accordance with the recommendations issued by the 2006 Consensus Group. These findings represent a change in practice with the collaborative goal of improved patient care.